(untitled) (Conferencea, 2023)
A significant role in revealing the ideological content of a work belongs to literary characters. The general attitude towards the work and understanding of its ideological meaning depend on the degree of perception and understanding of the characters. Literary characters reflect the generalized experience of the writer and express the most essential properties of people of our time or the era of the past. Literary characters are various types of people who reveal their character in specific historical conditions. The social significance of working on literary characters and the insufficient theoretical development of the problem of studying characters in institute determined the relevance of the study. The purpose of the article is to reveal methods for analyzing literary characters in literature lessons.